DIPG-34. Life and End-of-Life after Diffuse Intrinsic Pontine Glioma diagnosis. (3rd June 2022) - Pejenaute, Idoya Serrano; López-Almaráz, Ricardo; Echebarria, Aizpea; Adán, Rosa; De Pedro, Jimena; Gonzalez, Paula; Sanchez, Jesús; López-Bayón, Julio; Astigarraga, Itziar; García-Ariza, Miguel
Abstract: INTRODUCTION AND OBJECTIVES: Despite advances in pediatric oncology, Diffuse Intrinsic Pontine Glioma's (DIPG) life expectancy remains <10% at 2 years, and the mean survival time is 8-10 months from diagnosis. Its location associates multiple symptoms of complex management that condition their quality of life. The aim is to review our experience in the clinical course of the disease and the involvement of palliative care (PC). METHODS: Single-centre retrospective study of patients <18 years diagnosed with DIPG between 2011-2022. A review of the electronic medical record was carried out, recording demographic data, oncological treatments, PC and advance care planning (ACP). RESULTS: We registered 14 patients (2 alive). Median age at diagnosis was 6.4 years (range 3.5-11.9). Median survival from diagnosis was 9.6 months (range 0.5-18) and 3.8 months from progression (range 0.1-12). At diagnosis, 92% received oncological treatment (radiotherapy 75%, chemotherapy 41%, oncolytic viruses 21%, partial resection 8%). After progression, 4 patients received metronomic chemotherapy or re-irradiation and in the last month of life 2 received chemotherapy. In the last 3 months of life, 64% were admitted at least once for progression or end-of-life. In the last month, all received oral dexamethasone. Follow-up by PC team was provided in 64%, with first contact in the last month of life in 36%. ACP was recorded in 4 patients, all of them followed up for PC. Death occurred at home in 33%, hospital in 58%. Palliative sedation was used in 5 patients. CONCLUSIONS: Despite the known prognosis of DIPG, some patients continue receiving oncological treatment after progression and in the last month of life. Contact with PC teams occurred mainly at advanced disease stage. Median survival of children with DIPG is below one year, with multiple symptoms in the progression phase. Therefore, early follow-up by PC teams is recommended.